THE CORRELATION BETWEEN THE RISK OF ANEMIA IN PREGNANT WOMEN AND THEIR ADHERENCE TO PRENATAL CARE VISITS - Nur Fitriyah (Universitas Karya Husada Semarang, 2024)
The prevalence of anemia in pregnant women is still quite high, namely (48.9%). The aim of this study was to determine the relationship between Antenatal Care visits and the risk of anemia in pregnant women in Bima Regency, West Nusa Tenggara. This research is Correlative Analytical with a cross-sectional approach. where the population is 202 pregnant women for the period January-June 2023, while the sample is 51 pregnant women in the third trimester using a total sampling technique. The dependent variable of the research is the risk of anemia in pregnant women, while the independent variable is Compliance with Antenatal Care Visits for Pregnant Women. Data was obtained by looking at the results of examinations in the KIA book for pregnant women and checking hemoglobin with digital Hb. In this study, primary data was obtained by examining the KIA books of pregnant women and checking hemoglobin. Meanwhile, secondary data consists of data on the number of pregnant women in the third trimester. Data analysis in this study consisted of univariate analysis and bivariate analysis. Bivariate analysis uses the chi-square statistical test. The results of the study showed that there was a relationship between pregnant women's compliance with antenatal care visits and the risk of anemia with a value of P = 0.000.